Executive summary: Japanese guidelines for adult asthma (JGL) 2021 - Akio Niimi; Koichi Fukunaga; Masami Taniguchi; Yoichi Nakamura; Etsuko Tagaya; Takahiko Horiguchi; Akihito Yokoyama; Masao Yamaguchi; Makoto Nagata (Allergology International, 2023)
Asthma is characterized by chronic airway inflammation, variable airway narrowing, and sensory nerve irritation, which manifest as wheezing, dyspnea, chest tightness, and cough. Longstanding asthma may result in airway remodeling and become intractable. Despite the increased prevalence of asthma in adults, asthma-associated deaths have decreased in Japan (0.94 per 100,000 people in 2020). The goals of asthma treatment include the control of symptoms and reduction of future risks. A functional partnership between physicians and patients is indispensable for achieving these goals. Long-term management with medications and the elimination of triggers and risk factors are fundamental to asthma treatment. Asthma is managed via four steps of pharmacotherapy (“controllers”), ranging from mild to intensive treatments, depending on disease severity; each step involves daily administration of an inhaled corticosteroid, which varies from low to high dosage. Long-acting β2 agonists, leukotriene receptor antagonists, sustained-release theophylline, and long-acting muscarinic antagonists are recommended as add-on drugs. Allergen immunotherapy is a new option that is employed as a controller treatment. Further, as of 2021, anti-IgE antibody, anti-IL-5 and anti-IL-5 receptor α-chain antibodies, and anti-IL-4 receptor α-chain antibodies are available for the treatment of severe asthma. Bronchial thermoplasty can be performed for asthma treatment, and its long-term efficacy has been reported. Algorithms for their usage have been revised. Comorbidities, such as allergic rhinitis, chronic rhinosinusitis, chronic obstructive pulmonary disease, and aspirin-exacerbated respiratory disease, should also be considered during the treatment of chronic asthma. Depending on the severity of episodes, inhaled short-acting β2 agonists, systemic corticosteroids, short-acting muscarinic antagonists, oxygen therapy, and other approaches are used as needed (“relievers”) during exacerbation.